42x^-11=14

Simple and best practice solution for 42x^-11=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42x^-11=14 equation:



42x^-11=14
We move all terms to the left:
42x^-11-(14)=0
We add all the numbers together, and all the variables
42x-25=0
We move all terms containing x to the left, all other terms to the right
42x=25
x=25/42
x=25/42

You can always share this solution

See similar equations:

| 6x-38=5x-29 | | 2x-19=-1 | | 4/9(9-27/16)=x | | x=(1.15x)=97500 | | 6x+57-24=75 | | .6x+3=5x?8 | | 97500=x+1.15x | | 6x+57-24=6 | | x=74.93+0.15(x) | | x+.13x=75 | | 3x+7-10=6 | | 2x-1÷3=9 | | 9-3m=-m-(4m+1) | | N-5=3n+5 | | 70x+80x=225 | | 5-(4x+8)=5-4x-8 | | 3x+5+2x=5(2+x) | | 121/x=55/5 | | -1.7(2x-5.2=34 | | 8y-10-4y+7=0 | | x^2-27x+139=0 | | 4/6x=2,800 | | 76x+76=?76x+76 | | ?76x+76=76x+76 | | 1-2k=1-2k | | r+2=11-2r | | -2x-6-4x=2-2x-5x | | 1/3=c/6 | | 27-(2c+3=2(c+7)+c | | -5r-2=r+2-5r | | 6x+9x+9=90 | | -3x-7x-13=-7x+2 |

Equations solver categories